Facial palsy during the COVID‐19 pandemic. Issue 1 (7th November 2020) - Codeluppi, Luca; Venturelli, Francesco; Rossi, Jessica; Fasano, Antonio; Toschi, Giulia; Pacillo, Francesca; Cavallieri, Francesco; Giorgi Rossi, Paolo; Valzania, Franco
Abstract: Objective: To compare the incidence and clinical features of individuals presenting in emergency rooms (ER) with facial palsy during the Italian COVID‐19 outbreak and in the same period of 2019. Methods: We retrospectively reviewed the medical records for all accesses to the six ER in the province of Reggio Emilia, Italy, during the first phase of the COVID‐19 pandemic (27 February‐3 May 2020) to identify all cases of diagnosed facial palsy. Clinical information was retrieved for each patient and compared with that of facial palsy cases presenting in 2019. Result: Between 27 February and 3 May 2020, 38 patients presented to provincial ERs for facial palsy; in 2019, there were 22 cases, for an incidence rate ratio of 1.73 (95% CI 1.02–2.92) for the 2020 cohort. Of the 2020 cohort, eight patients (21%) presented with active or recent symptoms consistent with COVID‐19 infection, compared with 2 (9%) in 2019 ( p  = .299); one was tested and resulted positive for SARS‐CoV‐2 . Moreover, patients were younger (−11 years, p  = .037) than those of the previous year and manifested a longer lag (+1.1 days, p  = .001) between symptoms onset and ER presentation. Conclusion: We observed a higher occurrence of facial palsy during the COVID‐19 outbreak compared to the same period of the previous year; 21% of patients presenting with facial palsy had active or recent symptoms consistent with SARS‐CoV‐2 infection, suggesting an excess risk of facial palsy during or after COVID‐19. These patients searched for medical attention later, probably because of the fear of contracting COVID‐19 during assistance. Abstract : The objective of this study is to describe the clinical features of individuals presenting with facial palsy during the Italian COVID‐19 outbreak. We retrospectively reviewed the medical records for all accesses to the emergency departments in the province of Reggio Emilia, Italy, during the first phase of the COVID‐19 pandemic (27 February‐3 May 2020) to identify all cases of diagnosed facial palsy. We observed a higher occurrence of facial palsy during the COVID‐19 outbreak compared to the same period of the previous year; 21% of patients presenting with facial palsy had active or recent symptoms consistent with SARS‐CoV‐2 infection, suggesting a potential correlation.